Childhood acute lymphoblastic leukemia survival and spatial analysis of socio-environmental risks in Mexico - Calderon-Hernandez, Jaqueline; Jarquin-Yañez, Lizet; Reyes-Arreguin, Luis; Diaz-Padilla, Luis A.; Gonzalez-Compean, Jose Luis; Gonzalez-Montalvo, Pablo; Rivera-Gomez, Rebeca; Villanueva-Toledo, Jairo R.; Pech, Kristal; Arrieta, Oscar; Leal, Yelda A. (Frontiers in Oncology, 2023)
Background. Acute Lymphoblastic Leukemia (ALL) etiology remains largely unknown; incidence patterns by age, sex, and geographical distribution suggest a potential environmental role. Aim. To identify ALL clusters from four contrasting urban areas of Mexico and to characterize the sources of environmental carcinogens. Methods. Hospital-based-ALL cases (n=443) diagnosed in children <19 years old from Metropolitan Zones of Merida and San Luis Potosi, State of Mexico, and Tijuana were analyzed (2015-2020). ALL cases were coded according to the International Classification of Diseases for Oncology. ALL clusters were identified by Kernel Density, and excess risk was estimated. Data of PM2.5 (Particulate matter ≤2.5) concentrations measured by community-monitoring stations were analyzed. Geocoded datasets of benzene, polycyclic aromatic hydrocarbons, and PM2.5 sources were analyzed to characterize patterns of exposure in ALL clusters. Results. The survival rate for ALL ranged from 61.5-78.6%. Seven ALL clusters with excess risk (RR 1.4 - 2.3 p<0.05) were identified. The carcinogens sources included artisanal brick kilns, gas stations, cement works, carpentry, paint and chemical manufacturing establishments. PM2.5 levels ranged from 15 to 37 µg/m3 among study areas. Conclusion. ALL clusters were identified at the community level, the excess risk could be explained by small-carcinogen sources. Levels of PM2.5 in outdoor air ranged from 3 to 6 times above WHO air-quality guide. Health care providers must raise awareness of the increased risk of ALL in children living near sources of environmental carcinogens; cancer control and prevention strategies must be steered from a multi-sectoral and multi-actions perspective to protect children's health.